Controlled Release Ultrasonic-Coated Drug-Eluting Stent with Multilayers of Chitosan and Curcumin - Apitalau, Jeremia Frandy; Listyarifah, Dyah; Adhyatmika; Noviana, Eka; Yulianto, Heribertus Dedy Kusuma (Recent Advances in Drug Delivery and Formulation, 2026)
<span class=
Keywords: release kinetic